Predictors and Impact of Sulcal SAH after Mechanical Thrombectomy in Patients with Isolated M2 Occlusion - Kim, D.Y.; Baik, S.H.; Jung, C.; Kim, J.Y.; Han, S.-G.; Kim, B.J.; Kang, J.; Bae, H.-J.; Kim, J.H. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: Data on SAH after M2 mechanical thrombectomy are limited. We aimed to determine the prevalence of sulcal SAH after mechanical thrombectomy for M2 occlusion, its associated predictors, and the resulting clinical outcome.MATERIALS AND METHODS: The study retrospectively reviewed the data of patients with acute ischemic stroke who underwent mechanical thrombectomy for isolated M2 occlusion. The patients were divided into 2 groups according to the presence of sulcal SAH after M2 mechanical thrombectomy. Angiographic and clinical outcomes were compared. Multivariable analysis was performed to identify independent predictors of sulcal SAH and unfavorable outcome (90-day mRS, 3–6).RESULTS: Of the 209 enrolled patients, sulcal SAH was observed in 33 (15.8%) patients. The sulcal SAH group showed a higher rate of distal M2 occlusion (69.7% versus 22.7%), a higher of rate of superior division occlusion (63.6% versus 43.8%), and a higher M2 angulation (median, 128° versus 106°) than the non-sulcal SAH group. Of the 33 sulcal SAH cases, 23 (66.7%) were covert without visible intraprocedural contrast extravasation. Distal M2 occlusion (OR, 12.04; 95% CI, 4.56–35.67; P < .001), superior division (OR, 3.83; 95% CI, 1.43–11.26; P = .010), M2 angulation (OR, 1.02; 95% CI, 1.01–1.04; P < .001), and the number of passes (OR, 1.58; 95% CI, 1.22–2.09; P < .001) were independent predictors of sulcal SAH. However, covert sulcal SAH was not associated with an unfavorable outcome (P = .830).CONCLUSIONS: After mechanical thrombectomy for M2 occlusion, sulcal SAH was not uncommon and occurred more frequently with distal M2 occlusion, superior division, acute M2 angulation, and multiple thrombectomy passes (≥3). The impact of covert sulcal SAH was mostly benign and was not associated with an unfavorable outcome.AISacute ischemic strokeCAcontact aspirationEVTendovascular treatmentGREgradient recalled-echoICHintracerebral hemorrhageMTmechanical thrombectomymTICImodified TICISRstent retrieverSSsulcal SAH